Pengaruh Kinerja Keuangan Terhadap Belanja Modal Pemerintah Daerah Kota di Sumatera - Novrianto Ramadhani; Sandrayati; Rosy Armaini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Law No. 1 of 2022 mandates that capital expenditure allocation must be at least 40% of regional expenditure. Regional autonomy provides space for local governments to independently manage their finances. However, major cities in Sumatra still allocate a relatively small portion to capital expenditure. This research adopts a quantitative approach, utilizing secondary data extracted from regional government financial statements spanning the years 2019 to 2023. The findings reveal that fiscal autonomy at the regional level exerts a positively correlated and statistically significant influence on capital spending, while effectiveness has a negative and significant effect on capital expenditure. Meanwhile, the degree of contribution from Regional-Owned Enterprises (BUMD) does not affect capital expenditure. Collectively, the independent variables influence capital expenditure. Increasing regional financial independence encourages capital expenditure, but higher effectiveness leads to a decrease in capital expenditure. The suboptimal contribution of BUMD is attributed to less optimal management. Local governments are advised to optimize local revenue, balance capital expenditure allocation, and improve BUMD governance.